Iatrogenic intracranial hypotension complicated to dural venous sinus thrombosis and lobar hemorrhage: A case report - Hidayatullah Hamidi, MD; Mohammad Iqbal Haqyar, MD (Radiology Case Reports)
Iatrogenic intracranial hypotension is a known complication of spinal anesthesia that can lead to more severe conditions, such as dural or cerebral venous sinus thrombosis (CVST).This report presents a case of intracranial hypotension in a young woman after lumbar anesthesia for a cesarean section that was complicated by CVST and subsequently by lobar hemorrhage, clinically presenting with severe headache and seizures. The diagnosis was made via cerebral magnetic resonance (MR) imaging, and the patient was treated medically.This case study aimed to assist clinicians in considering the possible complications of intracranial hypotension when evaluating patients with a recent history of spinal procedures, leading to early diagnosis and treatment to prevent devastating consequences.